First you'd have to eliminate one of the variables, so which I used y. So to get rid of y, you need to multiply the whole equation, 3x+y=8, by 3. Which then you get 9x+3y=24.
On the second equation, it's stays the same. 5x+3y=8, except you chane the value of the number, so if it's positive change it to negative and vice versa.
So now you have -5x-3y=-8 and 9x+3y=24.
9x + 3y =24
-5x - 3y = 8
if you combine the terms, you'll see y is removed from the equation 3y-3y=0.
You're left with 4x=16, which x is 4.
Now you can substitute 4 for x to find y. Just use one of the equations to do this to, try 3x+y=8.
3(4)+y=8.
12+y=8
y=-4.
If you need the answer to be in a point form, it's (4,-4)